Effects of intramuscular fat on meat quality and its regulation mechanism in Tan sheep - Zhang, Xueying; Liu, Chongyang; Kong, Yuanyuan; Li, Fadi; Yue, Xiangpeng (Frontiers in Nutrition, 2022)
Intramuscular fat (IMF) contributes importantly to various aspects of meat quality, and genetic regulation is an effective pathway to improve IMF deposition in sheep. In this study, we systematically explored the effect of IMF content on meat quality in Tan sheep and investigated the regulatory mechanism of flavor precursors metabolism and IMF deposition. The results revealed that IMF significantly affected meat color, total muscle fiber numbers, and muscle fiber types in Tan sheep. Widely-targeted metabolomic analysis showed that amino acids were the main differential flavor precursors between lambs with different IMF content. Importantly, the comparison of fatty acid profiles revealed that saturated fatty acids and monounsaturated fatty acids are beneficial for IMF deposition. Furthermore, integrated analysis between metabolome and transcriptome indicated that MME is a key gene resulting in the reduction of amino acids in lambs with high IMF content; and the joint analysis between fatty acid profiles and transcript profiles showed that ADIPOQ, FABP4, PLIN1, PPARGC1A, SLC2A1 accelerated IMF deposition through positive regulation of saturated fatty acids and monounsaturated fatty acids metabolism. These results revealed key changes in meat quality affected by IMF content and the corresponding genetic mechanism, which may provide a new insight for understanding the IMF differential deposition and for improving meat quality in Tan sheep.